IMPLEMENTASI TOTAL QUALITY MANAGEMENT (TQM) DI PENDIDIKAN DASAR - Sri - Marmoah (Perspektif Ilmu Pendidikan, 2019)
Total Quality Management is a procedural method used in improving the quality of education in schools. This study aims to describe the implementation of Total Quality Management in primary education. This research was conducted in five Girimarto Subdistrict clusters in the year 2018. The research samples were five elementary schools divided into five clusters. Data collection techniques using non-test techniques that are using questionnaires or questionnaires to determine the success criteria for applying TQM in education to principals and teachers. The results of the study showed maximum results. The average acquisition of questionnaire calculations for school principals is 97.00 with a very good category, while the questionnaire for teachers is 94.00 with a very good category. The overall average obtained is 95.50 with a very good category. If viewed from the overall average obtained, it can be concluded that the application of TQM in education in Girimarto Subdistrict is in very good criteria. Thus, the school is concerned about asking for more primary needs in the provision of educational assistance, so that schools produce quality output.